2024
DOI: 10.3390/v16010080
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Astroviruses in Different Animal Species in Poland

Konrad Kuczera,
Anna Orłowska,
Marcin Smreczak
et al.

Abstract: Astroviruses (AstVs) are small RNA viruses characterized by a high mutation rate, the ability to recombine, and interspecies transmission, which allows them to infect a multitude of hosts including humans, companion animals, and farmed animals as well as wildlife. AstVs are stable in the environment, and their transmission is usually through the fecal–oral route or via contaminated water and food. Although direct zoonotic transmission was not confirmed, interspecies transmission events have occurred or have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In this study, we aimed to address this knowledge gap by conducting AstV detection in wild animals, such as bats and rodents, which play crucial roles in viral transmission [ 22 25 ]. We evaluated the infection rates and genetic features of the viral strains, the detection results revealed that wild boars exhibited the highest AstV infection rate (24.4%), consistent with their known high tolerance to AstV infections [ 26 ]. Unlike the significantly high infection rates observed in domestic pigs, the extensive habitat range of wild boars reduces the risk of fecal-oral transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to address this knowledge gap by conducting AstV detection in wild animals, such as bats and rodents, which play crucial roles in viral transmission [ 22 25 ]. We evaluated the infection rates and genetic features of the viral strains, the detection results revealed that wild boars exhibited the highest AstV infection rate (24.4%), consistent with their known high tolerance to AstV infections [ 26 ]. Unlike the significantly high infection rates observed in domestic pigs, the extensive habitat range of wild boars reduces the risk of fecal-oral transmission.…”
Section: Discussionmentioning
confidence: 99%